Literature of Review Influence Word Of Mouth, Satisfaction and Brand Image of Purchases Duck Queen Frozen in Bekasi - Riki Nur Allpiah (Draf Solusi Indonesia, 2023)
This research is a literature review that examines theinfluence of Word of Mouth, Satisfaction and BrandImage of Purchases. This research focuses on frozenbusinesses located in Bekasi City. This research willreveal the relationship between the independentvariable and the dependent variable. This researchuses a quantitative design with a customerpopulation from Frozen Duck Queen with samplesusing the Slovin approach. This research will use SPSSstatistical tools to process research data and answerresearch hypotheses.